Psychological measurement of hallucinatory experiences and apparitional experiences - Parra, Alejandro (2008)
An apparition is a visual experience in which there appears to be a person or animal present, often in connection with an agent who is dying or undergoing some other crisis. A number of hypotheses were tested: people seeing apparitions and having other apparition-like experiences (experients) have a higher capacity for absorption, fantasy and dissociation proneness, high neuroticism and schizotypy and score higher on three sensory modalities of hallucinatory experience than non-experients. This study demonstrated the viability of adopting a psychological approach in order to better understand the apparitional experience.